Fintech for Sustainable Street Vending Business : An Empirical Evidence from Indian Market - Swain, Bideharanjan; Kerketta, Sujata; Dey, Sanjeeb Kumar (AMC Indian Journal of Entrepreneurship, 2025)
Purpose : The purpose of the paper was to investigate the factors that influenced the adoption of fintech for the sustainability of street vending businesses in the Indian market, based on the UTAUT 2 Model. Design/Methodology/Approach : Using the convenience sampling technique, we collected data from 154 respondents, of which 120 respondents’ responses were suitable for further analysis, and we applied statistical tools and techniques such as descriptive analysis, correlation, ANOVA, and regression analysis using the SPSS application. Findings : This study found that performance expectancy (PE) and behavioral intention (BI) had a positively significant effect on the adoption of fintech among street vending businesses in Cuttack City. Meanwhile, effort expectancy (EE), perceived reliability (PR), self-efficacy (SE), nervousness (Ner), social influence (SI), and facilitation condition (FC) imposed insignificant impact on fintech adoption. Additionally, fintech adoption also influenced street vending business sustainability positively. Practical Implications : The street vending business unquestionably boosted its performance by leveraging fintech through the UTAUT 2 model, significantly enhancing its financial assistance. Furthermore, several recommendations and practical suggestions were provided to the government, policymakers, and aspiring researchers to enhance the street vending businesses’ sustainability through fintech adoption. Originality/Value : The ongoing participation of street vendors was instrumental in sustaining India’s thriving economy by providing employment and essential services to a significant portion of the population, thereby enriching urban life and bolstering the national economy in the digital era.